2021
DOI: 10.1111/ddg.14427
|View full text |Cite
|
Sign up to set email alerts
|

Acute pruritic rash on a young woman after a restrictive diet

Abstract: A 19-year-old woman came to the Emergency Department with a 5-day history of an intensely pruritic rash. She reported it had started on her cleavage and 48 hours later, it had spread to her back, neck, and abdomen. Pruritus had slightly subsided without treatment by the time she went to the Emergency Department. Her previous medical history was unremarkable. She denied any systemic symptoms, taking any medication or history of previous eruptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In a case series of nine patients, Goh et al 11 found that 33.3% of their cases were on KD before PP appearance. Furthermore, several other cases have reported the induction of PP following KD commencement with a satisfactory improvement of the lesions following the reintroduction of carbohydrates 7,11–23 . In total, we reviewed 22 cases of PP manifested following KD including two cases among our patients.…”
Section: Ref No Age/gender Duration Of Diet Before Pp Onset (Day) Tre...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a case series of nine patients, Goh et al 11 found that 33.3% of their cases were on KD before PP appearance. Furthermore, several other cases have reported the induction of PP following KD commencement with a satisfactory improvement of the lesions following the reintroduction of carbohydrates 7,11–23 . In total, we reviewed 22 cases of PP manifested following KD including two cases among our patients.…”
Section: Ref No Age/gender Duration Of Diet Before Pp Onset (Day) Tre...mentioning
confidence: 99%
“…International Journal of Dermatology 2022, 61, 779-782 reintroduction of carbohydrates. 7,[11][12][13][14][15][16][17][18][19][20][21][22][23] In total, we reviewed 22 cases of PP manifested following KD including two cases among our patients. Most of the patients were female (18/22; 81.8%) with an average age of 24.9 years old.…”
mentioning
confidence: 99%